2015
DOI: 10.1136/bjsports-2015-094622
|View full text |Cite
|
Sign up to set email alerts
|

The psychological factor ‘self-blame’ predicts overuse injury among top-level Swedish track and field athletes: a 12-month cohort study

Abstract: The coping behaviour self-blame replaced training load in an integrated explanatory model of overuse injury risk in athletes. What seemed to be more strongly related to the likelihood of overuse injury was not the athletics load per se, but, rather, the load applied in situations when the athlete's body was in need of rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…The findings show that one of the most frequently used measures of load is the session RPE,117 120–124 127 146 150 152 153 175 178 179 or similar cross-products of training duration and subjectively reported intensity 104 105 149. These tools are particularly common in team sports, and have the advantage of combining external (duration) and internal (rating of perceived exertion) load, which may aid in revealing fatigue 26 30.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 98%
See 2 more Smart Citations
“…The findings show that one of the most frequently used measures of load is the session RPE,117 120–124 127 146 150 152 153 175 178 179 or similar cross-products of training duration and subjectively reported intensity 104 105 149. These tools are particularly common in team sports, and have the advantage of combining external (duration) and internal (rating of perceived exertion) load, which may aid in revealing fatigue 26 30.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 98%
“…These include psychological stressors, such as negative life-event stress,22 32 197–203 daily hassles32 204–207 and sports-related stress (eg, feeling of insufficient breaks and rest, stiff and tense muscles, and feeling vulnerable to injuries),117 133 207 but also personality variables such as trait anxiety,22 32 199 205 208 209 state anxiety,203 stress susceptibility,205 type A behaviours,210 trait irritability205 and mistrust,22 as well as maladaptive coping strategies 22 149 205 211…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some known risk factors are not explicitly listed (eg, genotype, psychological state, muscle fibre type, etc) and some risk factors are yet to be identified. As just one example, workloads may effect certain psychological variables (eg, commitment to training, self-blame, perceived stress/fatigue, etc), which could subsequently alter match/training behaviour and change injury risk 48 72. Moreover, the interactions/confounding relationships between various risk factors are not detailed.…”
Section: An Updated Injury Aetiology Model—incorporating the Effects mentioning
confidence: 99%
“…Previous studies have shown that illnesses sustained during championships are commonly caused by infection, allergies or are environmentally related,5–7 but no clear risk indicators have been identified. Regarding other types of distress among athletes, psychological and behavioural indicators stand out as early markers in sports where overuse is an important cause of health problems 8 9. Athletes become cognitively aware of perceptions indicating a health problem predominantly if these perceptions are unexpected or cannot be explained.…”
Section: Introductionmentioning
confidence: 99%